Environment, climate change, and global governance : report (The Centre for International Governance Innovation WaterlooCA, 2008)
Discusses how the climate change issue can be addressed and how successful climate policy should be measured. Seeks to identify the key actors, their roles as well as the role of an informal group of leaders.
Keywords: CLIMATE CHANGE